Biblioteconomia é coisa de mulher? Relações de gênero e estereótipos na região Centro-Oeste (1962-2021) - Basilio, Esdra (2023)
This thesis exposes an investigation into the area of Librarianship from the perspective of gender relations studies. I present an analysis of the librarian profession with the purpose of historically showing that the profession went through a process of feminization and, in this sense, I point out the implications that this feminization entailed for the field of knowledge. The proposal is to discuss the connections between the low valuation of the profession and the connection with the fact that the profession is mostly exercised by women. I used feminist epistemologies and the theory of gender relations studies based on the contributions of Perrot (2005), Rago (1998) and Scott (2012), among other authors, to understand the dynamics of power relations that circumscribe the profession. The methodology used was a thematic oral history, from the perspective of Alberti (2013), Meihy (1996) and Portelli (2001). The narratives of five librarians, who work in the Midwest region, were the main sources of the research, characterizing this region as the locus of analysis, more specifically the federal universities that offer the undergraduate course in Librarianship, namely: the University of Brasília, the Federal University of Goiás and the Federal University of Rondonópolis in the period between 1962-2021. The research confirmed that disputes and power games make up the field of Librarianship, in a comprehensive way where gender hierarchies are reaffirmed.